The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pola.28618
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐blue light‐emitting polyfluorenes containing spiro[fluorene‐9,9′‐thioxanthene‐S,S‐dioxide] isomers

Abstract: Blue light‐emitting polyfluorenes, PPF‐FSOs and PPF‐SOFs were synthesized via introducing spiro[fluorene‐9,9′‐thioxanthene‐S,S‐dioxide] isomers (2,7‐diyl and 2′,7′‐diyl) (FSO/SOF) into the poly[9,9‐bis(4‐(2‐ethylhexyloxy) phenyl)fluorene‐2,7‐diyl] (PPF) backbone, respectively. With the increasing contents of FSO and SOF moieties, the absorption and PL spectra of PPF‐FSOs show slight red shift, while that of PPF‐SOFs exhibit blue shift, respectively. The HOMO and LUMO levels reduce gradually with increasing SOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The LUMO levels of the polymers were obtained from the HOMO levels and corresponding optical bandgaps. Thus, the calculated LUMO levels for the polymers were − 2.56, [55]. Table 2 compares the electrochemical properties of all copolymers.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…The LUMO levels of the polymers were obtained from the HOMO levels and corresponding optical bandgaps. Thus, the calculated LUMO levels for the polymers were − 2.56, [55]. Table 2 compares the electrochemical properties of all copolymers.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…47 In addition, Li et al 48 reported SpDBTS-based fluorescent emitters and host materials in which donor units such as carbazole, phenyl-carbazole, and diphenylamine were substituted at the 2 0 ,7 0 -position of the sulfonyl rings and the perpendicular arrangement of the spirofluorene ring avoids the strong intermolecular interaction. 49 Peng et al 50 reported a blue-fluorescent emitting polymer with SpDBTS as an acceptor unit in which the donor units were introduced at the 2,7-position of the fluorene ring and the 2 0 ,7 0 -position of the sulfonyl rings. This introduction of a donor at the 2 0 ,7 0 -position of the sulfonyl rings shows poor conjugation along the donor-acceptor-donor backbone by the sp 3 -carbon and sulfonyl groups, which shows blue-shifted emission with intramolecular charge transfer characteristics between the donor and acceptor sulfonyl rings and the fluorene ring not involved in the emission acts as an appendage.…”
Section: Introductionmentioning
confidence: 99%
“…To enable access to deep‐blue PLEDs and improve the comprehensive performance of PFs, electron‐withdrawing units (e.g., 1,3,4‐oxadiazole, 1,2,4‐triazole, 2,4,6‐triphenyl pyridine, dibenzothiophene‐ S , S ‐dioxide (SO)) have been introduced into polymer backbones or side chains to enhance electron injection and balance charge transport 15–19 . Weak conjugate‐structured 20–21 or twisted polymer backbones 22–24 have also been designed to interrupt the conjugation of the polymer backbone and thereby achieve deep‐blue emission. However, incorporation of electron‐withdrawing groups into the polymer backbone leads to charge‐transfer (CT) from electron‐rich units to electron‐withdrawing groups, which results in bathochromic spectra and influences the color purity of blue emission 25,26 .…”
Section: Introductionmentioning
confidence: 99%